Performance comparison of two Olympus InnovX handheld x-ray analyzers for feasibility of measuring arsenic in skin in vivo – Alpha and Delta models. (May 2017) - Desouza, E.D.; Gherase, M.R.; Fleming, D.E.B.; Chettle, D.R.; O'Meara, J.M.; McNeill, F.E.
Abstract: The Figure-Of-Merit (FOM) performance, a combination of detection limit and dose, is compared between two generations of handheld X-Ray Fluorescence (XRF) spectrometers for the feasibility of in vivo XRF measurement of arsenic (As) in skin. The Olympus InnovX Delta model analyzer (40 kVp using either 37 or 17 μA) was found to show improvements in Minimum Detection Limit (MDL) using arsenic As-doped skin calibration phantoms with bulk tissue backing, when compared to the first generation InnovX Alpha model (40 kVp, 20 μA) in 120 s measurements. Differences between two different definitions of MDL are discussed. On the Delta system, an MDL of (0.462±0.002) μg/g As was found in phantoms, with a nylon backing behind to mimic bulk tissue behind skin. The equivalent and effective doses were found to be (10±2) mSv and 7×10 −3 μSv respectively for the Alpha and (15±4) mSv and 8×10 −3 μSv respectively for the Delta system in 120 s exposures. Combining MDL and effective dose, a lower (better) FOM was found for the Delta, (1.7±0.4) ppm mSv 1/2, compared to (4.4±0.5) ppm mSv 1/2 for the Alpha model system. The Delta analyzer demonstrates improved overall system performance for a rapid 2-min measurement in As skin phantoms, such that it can be considered for use in populations exposed to arsenic. Highlights: Second generation portable XRF system reports lower Arsenic detection limit. When excluded from calibration, <1 ppm error in predicted 5, 20 ppm As concentration. Effective dose of both generations of systems in stand mode is within ICRP limit.